(untitled) (Acta Scientiarum. Agronomy, 2019)
Knowledge on the dynamics of micronutrients in coffee tree assists nutritional diagnosis and fertilization management. Therefore, the objective of this study was to evaluate the concentration and accumulation of micronutrients in the leaves and fruits of Coffea canephora. The experiment was managed in crops propagated for 2.5 years in a split-plot-in-time scheme in which the main plots consisted of fertilized and not-fertilized plants, and the subplots stipulated the evaluation periods. The berries and leaves were collected every 28 days, starting from the first flowering to full maturity. The micronutrient content was determined by laboratory chemical analysis, and the accumulation of nutrients in the fruit (mg) was calculated by multiplying the dry matter of the berry (g) Ã— nutrient concentration (mg kgâˆ’1). The results showed that fertilization infers the zinc concentration in the fruits and the concentration for manganese, iron and zinc in the leaves in the determined periods. Micronutrient accumulation curves followed the simple sigmoidal model, with accumulation increasing considerably as a function of fruit growth. Thus, fertilization based on micronutrients must be divided over stages with higher accumulation rates, considering the specific requirement of each nutrient.